Reestructuración técnico administrativa en la empresa: Inversiones Stivali S.A.S ubicada en la ciudad de Bogotá D.C. (2017)
The technical and administrative restructuring of the company Inversiones Stivali S. A. S., Located in Bogotá D.C; Was carried out during the first half of 2017. Starting from a diagnosis in order to analyze the current situation of the company and identify the impact of external and internal factors on the organization, through the implementation of the PESTEL analysis, the SWOT matrix and the business self-diagnosis.